2012
DOI: 10.1021/ja300064t
|View full text |Cite
|
Sign up to set email alerts
|

Alkylthiol-Enabled Se Powder Dissolution in Oleylamine at Room Temperature for the Phosphine-Free Synthesis of Copper-Based Quaternary Selenide Nanocrystals

Abstract: Enhancement of Se solubility in organic solvents without the use of alkylphosphine ligands is the key for phosphine-free synthesis of selenide semiconductor nanocrystals (NCs). In this communication, we demonstrate the dissolution of elemental Se in oleylamine by alkylthiol reduction at room temperature, which generates soluble alkylammonium selenide. This Se precursor is highly reactive for hot-injection synthesis of selenide semiconductor NCs, such as Cu(2)ZnSnSe(4), Cu(InGa)Se(2), and CdSe. In the case of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
231
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(245 citation statements)
references
References 39 publications
14
231
0
Order By: Relevance
“…It was reported that selenium powder can be reduced by thiols which oxidized to disulfide. 74 Indeed GC-MS analysis confirmed the formation of dihexyl-disulfide (m/z = 234) resulting from oxidation of HTs ( Figure S5). A detailed discussion related to GC-MS data and further control experiments are provided in the Supporting Information File.…”
Section: Investigation Of Thementioning
confidence: 78%
“…It was reported that selenium powder can be reduced by thiols which oxidized to disulfide. 74 Indeed GC-MS analysis confirmed the formation of dihexyl-disulfide (m/z = 234) resulting from oxidation of HTs ( Figure S5). A detailed discussion related to GC-MS data and further control experiments are provided in the Supporting Information File.…”
Section: Investigation Of Thementioning
confidence: 78%
“…[23][24][25][26][27] Therefore, nontoxic, relatively simple, and reproducible approaches for the synthesis of PbSe NCs with controllable size and shape are of great fundamental and technological interest. [25] Herein, we report a new synthetic route for the preparation of high-quality PbSe NCs. In contrast to other PbSe synthetic methods that routinely require TOPO, we have used the more environmentally friendly solvent oleylamine (OLA).…”
Section: Introductionmentioning
confidence: 99%
“…[64][65] A highly reactive Se precursor by dissolving selenium in 1:1 mixture of amine and thiol is used instead of the typically used selenium-oleylamine mixture. 66 For ZnS shelling, a modified literature method was followed. 24 Details of the synthesis procedure are provided in the Experimental Section.…”
mentioning
confidence: 99%